Effect of gaspers on airflow patterns and the transmission of airborne contaminants within an aircraft cabin environment - Anderson, Michael D. (Kansas State University, 2012)
Due to the high occupant density and large number of travelers on commercial aircraft, it is crucial to limit the transport of contaminants and pathogens amongst passengers. In order to minimize the exposure of passengers to various contaminants of different sizes and characteristic, all mechanisms influencing airflow movement within an aircraft cabin need to be understood. The use of personal gaspers on commercial aircraft and their relation to airborne contaminants and pathogens transport is one such mechanism that was investigated. Tracer gas testing using carbon dioxide (CO[subscript]2) was conducted in a wide-body, 11-row Boeing 767 aircraft cabin mockup using actual aircraft components for air distribution. Three separate experiments were conducted investigating the effect of gaspers on the transport of contaminants. The first series of experiments focused on the effect of gaspers on longitudinal transport patterns within an aircraft cabin environment by measuring the concentration of tracer gas along the length of the aircraft cabin. The second experiment investigated what fraction of air a passenger inhales originates from a gasper in relation to the overall cabin ventilation. The final set of experiments determined if gaspers could limit close range person-to-person transmission of exhaled contaminants. Three separate sets of conclusions were drawn, one for each series of experiments. The first conclusion is that gaspers disrupt the longitudinal transport of contaminants within the aircraft cabin. The second conclusion is that less than 5% of the air inhaled by a passenger is originating from a gasper even with a gasper directed at the passenger's face. This low percentage is a result of the turbulent airflow within the aircraft cabin causing the gasper jet to quickly mix with the overall cabin ventilation air. The last conclusion is that gaspers can reduce person-to-person transmission of exhaled contaminants as much as nearly 90% in some cases. In other cases the gaspers are found to have negligible or negative impact on the transmission of contaminants. These conclusions are dependent upon where the tracer gas plume emanated from, the sampling location, and the configuration of gaspers around the tracer gas release point.
Keywords: Gaspers; Disease transmission; Commercial aircraft; Tracer gas; Mechanical Engineering (0548)